Relationship Between Macroeconomic Variables and Stock Market Price of Nepalese Insurance Companies - Shrestha, Purna Man (Economic Review of Nepal, 2019)
This study has examined the relationship between selected macroeconomic variables and the stock market of price of Nepalese insurance companies listed on Nepal Stock Exchange [NEPSE] for the period of July 2003 to June 2018. Monthly stock market index of Nepalese insurance companies of Nepal Stock Exchange has been taken as proxy of stock market price of insurance companies and interest rate, gold price, money supply, equity market capitalization, are taken as proxy of macroeconomic variables. This study has used cointegration test to examine the long-run relationship between variables and stock market of price of Nepalese insurance companies. The stationarity of the variables has been examined by applying Augmented Dickey-Fuller [ADF] test and Phillips-Perron [PP] test. When variables are found to be same order of integration then cointegration test is used to determine long-run relationship. This study concluded that there exists long-run equilibrium among the macroeconomic variables and stock market of price of Nepalese insurance companies listed on Nepal Stock Exchange. Similarly, this study has also followed vector error correction model to capture the short-run dynamics.